Osteo-immunological impact of radon spa treatment: due to radon or spa alone? Results from the prospective, thermal bath placebo-controlled RAD-ON02 trial - Eckert, Denise; Evic, Megi; Schang, Jasmin; Isbruch, Maike; Er, Melissa; Dörrschuck, Lea; Rapp, Felicitas; Donaubauer, Anna-Jasmina; Gaipl, Udo S.; Frey, Benjamin; Fournier, Claudia (Frontiers in Immunology, 2024)
Musculoskeletal disorders (MSDs) are associated with pain and lead to reduced mobility and quality of life for patients. Radon therapy is used as alternative or complementary to pharmaceutical treatments. According to previous reports, radon spa leads to analgesic and anti-inflammatory effects, but the cellular and molecular mechanisms are widely unknown. A previous study (RAD-ON01) revealed, that bone erosion markers like collagen fragments (C-terminal telopeptide, CTX) are reduced after radon spa treatment in serum of patients with degenerative MSDs. Within the scope of the prospective, placebo-controlled RAD-ON02 trial presented here, we analyzed the influence of radon and thermal spa treatment on osteoclastogenesis. From patient blood, we isolate monocytes, seeded them on bone slices and differentiated them in the presence of growth factors into mature osteoclasts (mOCs). Subsequent analysis showed a smaller fraction of mOCs after both treatments, which was even smaller after radon spa treatment. A significantly reduced resorbed area on bone slices reflects this result. Only after radon spa treatment, we detected in the serum of patients a significant decrease of receptor activator of NF-κB ligand (RANKL), which indicates reduced differentiation of OCs. However, other markers for bone resorption (CTX) and bone formation (OPG, OCN) were not altered after both treatments. Adipokines, such as visfatin and leptin that play a role in some MSD-types by affecting osteoclastogenesis, were not changed after both treatments. Further, also immune cells have an influence on osteoclastogenesis, by inhibiting and promoting terminal differentiation and activation of OCs, respectively. After radon treatment, the fraction of Treg cells was significantly increased, whereas Th17 cells were not altered. Overall, we observed that both treatments had an influence on osteoclastogenesis and bone resorption. Moreover, radon spa treatment affected the Treg cell population as well as the Th17/Treg ratio were affected, pointing toward a contribution of the immune This is a provisional file, not the final typeset article system after radon spa. These data obtained from patients enrolled in the RAD-ON02 trial indicate that radon is not alone responsible for the effects on bone metabolism, even though they are more pronounced after radon compared to thermal spa treatment.